Missed antenatal diabetes care appointments and neonatal outcomes for pregnancies with Type 1 and Type 2 diabetes. Issue 1 (20th September 2022) - Stafl, Lenka; Benham, Jamie L.; Frehlich, Levi; Donovan, Lois E.; Yamamoto, Jennifer M.
Abstract: Background: There is limited information regarding the association between missed appointments and neonatal outcomes for diabetes in pregnancy. Study Methods: This retrospective live birth cohort included pregnant women with Type 1 or 2 diabetes who attended specialized clinics from 2008 to 2020. The association between at least one missed antenatal diabetes appointments and outcomes were assessed using logistic regression and reported as adjusted odds ratios (aOR) (95% confidence interval). Mediation analyses were conducted to examine if above target HbA1c mediated these relationships. Results: The cohort included 407 and 902 women with Type 1 and 2 diabetes, respectively, of whom 25.1% and 34.5% missed at least one appointment. Women with Type 1 diabetes who missed an appointment were more likely to have a caesarean section (aOR 1.95 [1.15, 3.31]) and their babies more likely to be admitted to the neonatal intensive care unit (aOR 2.25 [1.35, 3.75]). Women with Type 2 diabetes who missed an appointment were more likely to have a large‐for‐gestational‐age infant (aOR 1.61 [1.13, 2.28]), and an extreme large‐for‐gestational‐age infant (aOR 1.69 [1.02, 2.81]) compared with women who did not miss appointments. Above target HbA1c mediated the relationship between missed appointments and caesarean delivery in Type 1 diabetes and large‐for‐gestational age and extreme large‐for‐gestational age in Type 2 diabetes. Conclusion: In individuals with Type 1 and 2 diabetes, there are differences in neonatal outcomes between those who missed an appointment compared to those who did not. It remains unclear if missed diabetes appointments are causative or a marker of other health behaviours or risk factors leading to neonatal morbidity.